Non-aqueous electrolyte and sodium ion battery
By using the non-aqueous electrolyte prepared by using three additives in sodium ion batteries, a solid solid electrolyte interface mask is formed, which solves the problem of electrolyte decomposition and poor circulation performance caused by excessive moisture in sodium ion batteries, and achieves excellent circulation performance and high temperature resistance.
Patent Information
- Application Number
- CN202411605280.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-03-11
AI Technical Summary
Excessive moisture content in sodium ion batteries leads to the decomposition of the electrolyte, affects the film formation and stability of the positive and negative electrode materials, and produces too much gas during the charge and discharge process, poor circulation performance, which leads to safety problems.
Three additives are used as composite additives, combining sodium salt and non-aqueous solvent to prepare a nonaqueous electrolyte solution. It is used in sodium ion batteries with a moisture content of 400ppm to form a solid solid electrolyte interface mask, inhibiting battery expansion and improving circulation performance and high temperature resistance.
It effectively inhibits the hydrolysis of sodium salt in the electrolyte and battery expansion, reduces the adverse effects of moisture introduced by the production process on battery performance, and improves the circulation performance and high-temperature storage performance of sodium ion batteries.
Smart Images

Figure CN119601769A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sodium ion batteries, and in particular relates to a non-aqueous electrolyte and a sodium ion battery. Background Art
[0002] Sodium-ion batteries and lithium-ion batteries have similar working principles, material systems, and component structures. The research on sodium-ion batteries can draw on the research experience of lithium-ion batteries, but it cannot be completely transplanted. Because the alkalinity of metallic sodium is stronger than that of metallic lithium, the surface of the positive electrode of sodium-ion batteries has a stronger binding effect with water than that of lithium-ion batteries; the hard carbon with disordered accumulation of some carbon layers is mainly amorphous, and has more mesoporous and microporous structures than the graphite negative electrode of lithium-ion batteries. The surface area is larger and it is easier for water to adhere, making it more difficult to remove water from the positive and negative electrode sheets of sodium-ion batteries. When the water content in sodium-ion batteries is too high, it will not only decompose the electrolyte, but also have a negative impact on the film formation and stability of the positive and negative electrode materials. In addition, sodium-ion batteries produce too much gas during the charge and discharge process, and have poor cycle performance, which will cause battery bulging and leakage, causing serious safety problems.
[0003] After the sodium-ion battery cells were dried using the traditional lithium-ion battery drying process, the water content of the positive and negative pole pieces was tested using the Karl Fischer coulometric method. The water content was 800-1000ppm and 300-500ppm, respectively, which is much higher than the process standard of 50-200ppm for lithium-ion batteries. In addition, after the pole pieces are dried, they will still absorb moisture from the air during the subsequent production process, causing the moisture content to exceed the standard. Currently, the moisture content in the pole pieces can only be guaranteed by controlling the dew point in the environment. To control the dew point in the environment, it is usually necessary to run equipment such as dehumidifiers, and the lower the dew point requirement, the greater the energy consumption. Therefore, finding a suitable method to control the moisture content in sodium-ion batteries and improve their safety performance is of great significance to the application of sodium-ion batteries. Summary of the invention
[0004] The purpose of the present invention is to solve the above technical problems, use three additives as composite additives, combine sodium salt and non-aqueous solvent to prepare a non-aqueous electrolyte, even if used in a sodium ion battery with a moisture content of 400ppm, it can still effectively inhibit battery expansion, so that the obtained sodium ion battery exhibits excellent cycle performance and high temperature resistance.
[0005] The non-aqueous electrolyte in the technical solution of the present invention comprises a sodium salt, a non-aqueous solvent and a composite additive, wherein the composite additive comprises a first additive, a second additive and a third additive, wherein the first additive is a compound containing a sulfur-oxygen bond in its structure, the second additive is a sodium salt compound, and the third additive is an imidazole compound.
[0006] Furthermore, the first additive is one or more of a cyclic sulfate compound, a cyclic sulfonate compound, and a fluorosulfonyl compound; and / or the second additive is one or more of sodium difluorooxalylborate (NaDFOB), sodium difluorophosphate (NaDFP), sodium bis(fluorosulfonyl)imide (NaFSI), and sodium acesulfame (NaA).
[0007] Further, the structural formula of the cyclic sulfate compound is wherein R1 to R4 are each independently a hydrocarbon group having 1 to 3 carbon atoms or a hydrogen atom, and n is 0 or 1;
[0008] And / or the structural formula of the cyclic sulfonate compound is wherein R5 to R14 are each independently a hydrocarbon group having 1 to 3 carbon atoms, a hydrogen atom or a fluorine atom, Where n is 0 or 1, where n is 1;
[0009] And / or the structural formula of the fluorosulfonyl compound is Among them, R15 represents a hydrocarbon group having 1 to 6 carbon atoms, an aromatic group having 6 to 10 carbon atoms, or a fluorine atom; phenyl fluorosulfonate is particularly preferred.
[0010] Preferably, the cyclic sulfate ester compound is one or more of vinyl sulfate, 4-methylethylene sulfate, 4-propylethylene sulfate, propylene sulfate, 4-methylpropylene sulfate and 4-propylpropylene sulfate, and vinyl sulfate is particularly preferred.
[0011] Preferably, the cyclic sulfonate compound is one or more of 1,3-propane sultone, 1,4-butane sultone, 1-propenyl-1,3-sultone, 1-propenyl-1-fluoro-1,3-sultone, 1-propenyl-1,2-difluoro-1,3-sultone, and 1-butenyl-1,4-sultone, and particularly preferably one or two of 1,3-propane sultone and 1-propenyl-1,3-sultone.
[0012] Furthermore, the mass of the first additive is 0.1-5.0%, preferably 0.2-3.0%, of the mass of the non-aqueous electrolyte; and / or the mass of the second additive is 0.1-10.0%, preferably 0.2-5.0%, of the mass of the non-aqueous electrolyte.
[0013] Furthermore, the cation of the third additive is one or more of lithium ion, sodium ion, imidazolium cation, and quaternary ammonium cation; the anion is an imidazolium anion, preferably a 4,5-dicyano-2-(trifluoromethyl)imidazolium anion.
[0014] The ionic salt in the third additive can capture moisture in the battery through hydrogen bonding, effectively inhibiting the degradation of the electrolyte solvent caused by the hydrolysis of sodium salt in the electrolyte, and maintaining the good ion conductivity of the electrolyte; at the same time, the nitrile group can interact with the hydrogen fluoride molecules in the electrolysis to reduce the parasitic reaction on the cathode side, and can also interact with the transition metal in the positive electrode material to form a strong SEI film, inhibiting the dissolution of transition metals during the cycle, and ensuring the reversible capacity of the sodium ion battery.
[0015] The second additive contains an oxalic acid skeleton, a phosphate skeleton or an -S=O- group. Combined with the first additive and the third additive, a solid electrolyte interface film (SEI film) with high thermal stability and high ion transmission capacity can be formed, which effectively inhibits the capacity decay of the sodium ion battery during high-temperature storage; the third additive is combined with the first additive and the second additive to help grow the NaF inorganic phase through the defluorination of the CF3 group in the anion, and at the same time promote the formation of the polymer phase, thereby producing a thinner and stronger SEI film with lower resistivity, which can reduce the loss of initial capacity.
[0016] Further, the structural formula of the imidazolium cation is The structural formula of the quaternary ammonium cation is Here, R16 to R19 each independently represent a hydrocarbon group having 1 to 6 carbon atoms.
[0017] Preferably, the third additive is one or more of 4,5-dicyano-2-(trifluoromethyl)imidazolium lithium salt, 4,5-dicyano-2-(trifluoromethyl)imidazolium sodium salt, 4,5-dicyano-2-(trifluoromethyl)imidazolium-1,3-dimethylimidazolium salt and 4,5-dicyano-2-(trifluoromethyl)imidazolium-trimethylethylammonium salt.
[0018] Furthermore, the mass of the third additive is 0.1 to 2.0% of the mass of the non-aqueous electrolyte, and preferably 0.5 to 1.5%.
[0019] The sodium salt in the present invention is not limited, and any sodium salt that can be used in sodium ion battery electrolyte can be used, including but not limited to one or more of sodium hexafluorophosphate (NaPF6), sodium perchlorate (NaC1O4), sodium trifluoromethylsulfinate (NaSO3CF3), sodium tetrafluoroborate (NaBF4), and sodium bis(trifluoromethylsulfonyl)imide (NaTFSI).
[0020] Furthermore, the concentration of the sodium salt in the non-aqueous electrolyte is 0.5 to 2.0 mol / L, preferably 0.8 to 1.2 mol / L.
[0021] Furthermore, the non-aqueous solvent is one or both of carbonates and carboxylates; the carbonates are one or more of cyclic carbonates and chain carbonates, including but not limited to one or more of propylene carbonate (PC), ethylene carbonate (EC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC); the carboxylates include but are not limited to one or more of methyl formate (MF), ethyl acetate (EA), propyl acetate (PA), and methyl butyrate (MB).
[0022] Furthermore, the non-aqueous solvent is a mixture of carbonate ester and carboxylate ester in a mass ratio of 7:3 to 9:1.
[0023] Furthermore, the carbonate is a mixture of cyclic carbonate and chain carbonate in a mass ratio of 3:7 to 1:1, preferably 3:5 to 5:7.
[0024] The non-aqueous electrolyte is obtained by mixing sodium salt, non-aqueous solvent and composite additives.
[0025] The present invention also provides a sodium ion battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and the above-mentioned non-aqueous electrolyte.
[0026] The positive electrode active material in the above-mentioned sodium ion battery positive electrode sheet is not limited, and any active material that can be used for the positive electrode of a sodium ion battery can be used, including but not limited to one or more of sodium cobalt oxide, sodium manganese oxide, sodium-based multi-transition metal compounds, transition metal sodium phosphate salts, and transition metal sodium fluorophosphate salts.
[0027] The negative electrode active material in the above-mentioned sodium ion battery negative electrode sheet is not limited. Any active material that can be used for the negative electrode of a sodium ion battery can be used, including but not limited to one or more of soft carbon, hard carbon, acetylene black, sodium titanate, and metals that can form alloys with sodium.
[0028] The separator in the above-mentioned sodium ion battery is not limited, and any separator that can be used for sodium ion batteries can be used, including but not limited to one or more of polypropylene film, polyethylene film, polyethylene / polypropylene / polyethylene composite film, cellulose non-woven film, and glass fiber film.
[0029] The preparation method of the sodium ion battery comprises the following steps: stacking the positive electrode sheet, the separator and the negative electrode sheet in order to obtain a bare cell, placing the bare cell in an outer package, injecting a non-aqueous electrolyte, and packaging and forming.
[0030] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:
[0031] (1) The three additives are combined as a composite additive to obtain a non-aqueous electrolyte that can form a strong solid electrolyte interface film on the positive and negative electrode surfaces of the sodium ion battery, effectively inhibiting the hydrolysis of the sodium salt in the electrolyte and the expansion of the battery;
[0032] (2) The obtained sodium ion battery reduces the possibility of adverse effects on battery performance caused by the inevitable introduction of moisture during the production process, reduces production costs, and improves the cycle performance and high-temperature storage performance of the sodium ion battery;
[0033] (3) The second additive contains an oxalic acid skeleton, a phosphate skeleton or a -S=O- group, and combined with the first additive and the third additive, can form an SEI film with high thermal stability and high ion transport capacity, effectively inhibiting the capacity decay of the sodium ion battery during high temperature storage;
[0034] (4) The ionic salt in the third additive can capture water in the battery through hydrogen bonding, effectively inhibiting the degradation of the electrolyte solvent caused by the hydrolysis of the sodium salt in the electrolyte, maintaining the good ion conductivity of the electrolyte, and ensuring the sodium ion transmission performance.
[0035] (5) The nitrile group in the third additive can interact with the hydrogen fluoride molecules in the electrolysis to reduce the parasitic reaction on the cathode side. It can also interact with the transition metal in the positive electrode material to form a strong SEI film, inhibit the dissolution of transition metals during the cycle, and ensure the reversible capacity of the sodium ion battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 The graph shows the cycle performance of the non-aqueous electrolytes of Example 1 and Comparative Example 3 for sodium ion batteries. DETAILED DESCRIPTION
[0037] The technical scheme of the present invention is further described below by specific examples and accompanying drawings. It should be understood that the specific examples described herein are only used to help understand the present invention and are not intended for specific limitations of the present invention. The accompanying drawings used herein are only for better illustrating the disclosed content of the present invention and do not have a limiting effect on the scope of protection. If not otherwise specified, the raw materials used in the embodiments of the present invention are all commonly used raw materials in the art, and the methods used in the embodiments are all conventional methods in the art.
[0038] In the present invention, the positive electrode active material NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2, conductive agent carbon black, and binder polyvinylidene fluoride are mixed in a weight ratio of 95.5:3.0:1.5, N-methylpyrrolidone is added, and the mixture is stirred and mixed to obtain a positive electrode slurry, which is coated on an aluminum foil, and then dried, cold pressed, cut, and welded to the tabs to obtain a positive electrode sheet for a sodium ion battery;
[0039] The negative electrode active material hard carbon, the conductive agent carbon black, the binder styrene butadiene rubber and carboxymethyl cellulose are mixed in a weight ratio of 95.0:1.0:2.0:2.0, and water is added and stirred to obtain a negative electrode slurry, which is coated on an aluminum foil, and then dried, cold pressed, cut and welded to obtain a negative electrode sheet for a sodium ion battery;
[0040] The diaphragm is made of porous polyethylene film.
[0041] Example 1
[0042] The non-aqueous electrolyte of this embodiment is a non-aqueous solvent obtained by mixing EC, PC, DEC and EMC in a mass ratio of 5:25:30:30, adding NaPF6 at a molar concentration of 1.0 mol / L, and then adding 1.0% by mass of vinyl sulfate and 4-methylethylene sulfate, 0.5% by mass of 1-propenyl-1,3-sulfonic acid lactone and sodium difluorooxalatoborate, and 1.0% by mass of 4,5-dicyano-2-(trifluoromethyl)imidazole lithium salt and mixing them evenly.
[0043] Example 2
[0044] The non-aqueous electrolyte of this embodiment is a non-aqueous solvent obtained by mixing EC, DEC and MF in a mass ratio of 30:50:20, adding NaPF6 at a molar concentration of 1.1 mol / L, and then adding 1.0% by mass of vinyl sulfate and 4-methylethylene sulfate, 0.5% by mass of 1-propenyl-1,3-sulfonic acid lactone and sodium difluorooxalatoborate, and 1.0% by mass of 4,5-dicyano-2-(trifluoromethyl)imidazole lithium salt and mixing them evenly.
[0045] Example 3
[0046] The non-aqueous electrolyte of this embodiment is a non-aqueous solvent obtained by mixing PC, EMC and PA in a mass ratio of 30:55:15, adding NaPF6 at a molar concentration of 1.2 mol / L, and then adding 1.0% by mass of vinyl sulfate and 4-methylethylene sulfate, 0.5% by mass of 1-propenyl-1,3-sulfonic acid lactone and sodium difluorooxalatoborate, and 1.0% by mass of 4,5-dicyano-2-(trifluoromethyl)imidazole lithium salt and mixing them evenly.
[0047] Example 4
[0048] The non-aqueous electrolyte of this embodiment is a non-aqueous solvent obtained by mixing EC, PC, DEC and EMC in a mass ratio of 5:25:30:30, adding NaPF6 at a molar concentration of 1.0 mol / L, and then adding 1.0% by mass of vinyl sulfate and 1,4-butane sultone, 0.5% by mass of phenyl fluorosulfonate and sodium bis(fluorosulfonyl)imide, and 1.0% by mass of 4,5-dicyano-2-(trifluoromethyl)imidazole sodium salt and mixing evenly.
[0049] Example 5
[0050] The non-aqueous electrolyte of this embodiment is a non-aqueous solvent obtained by mixing EC, PC, DEC and EMC in a mass ratio of 5:25:30:30, adding NaPF6 at a molar concentration of 1.0 mol / L, and then adding 1.0% by mass of vinyl sulfate and 4-methylethylene sulfate, 1.0% by mass of sodium difluorooxalatoborate, and 0.8% by mass of 4,5-dicyano-2-(trifluoromethyl)imidazole lithium salt and mixing them evenly.
[0051] Example 6
[0052] The non-aqueous electrolyte of this embodiment is a non-aqueous solvent obtained by mixing EC, PC, DEC and EMC in a mass ratio of 5:25:30:30, adding NaPF6 at a molar concentration of 1.0 mol / L, and then adding 1.0% by mass of 4-methylethylene sulfate, 0.8% by mass of 1-propenyl-1,3-sulfonic acid lactone, 2.0% by mass of sodium difluorooxalatoborate, and 1.5% by mass of 4,5-dicyano-2-(trifluoromethyl)imidazole lithium salt and mixing them evenly.
[0053] Example 7
[0054] The non-aqueous electrolyte of this embodiment is a non-aqueous solvent obtained by mixing EC, PC, DEC and EMC in a mass ratio of 5:25:30:30, adding NaPF6 at a molar concentration of 1.0 mol / L, and then adding 0.05% by mass of vinyl sulfate and 4-methylethylene sulfate, 0.5% by mass of sodium difluorooxalatoborate, and 1.0% by mass of 4,5-dicyano-2-(trifluoromethyl)imidazole lithium salt and mixing them evenly.
[0055] Example 8
[0056] The non-aqueous electrolyte of this embodiment is a non-aqueous solvent obtained by mixing EC, PC, DEC and EMC in a mass ratio of 5:25:30:30, adding NaPF6 at a molar concentration of 1.0 mol / L, and then adding 2.0% by mass of vinyl sulfate and 4-methylethylene sulfate, 1.5% by mass of 1-propenyl-1,3-sulfonic acid lactone, 0.5% by mass of sodium difluorooxalatoborate, and 1.0% by mass of 4,5-dicyano-2-(trifluoromethyl)imidazole lithium salt and mixing them evenly.
[0057] Example 9
[0058] The non-aqueous electrolyte of this embodiment is a non-aqueous solvent obtained by mixing EC, PC, DEC and EMC in a mass ratio of 5:25:30:30, adding NaPF6 at a molar concentration of 1.0 mol / L, and then adding 1.0% by mass of vinyl sulfate and 4-methylethylene sulfate, 0.5% by mass of 1-propenyl-1,3-sulfonic acid lactone, 0.05% by mass of sodium difluorooxalatoborate, and 1.0% by mass of 4,5-dicyano-2-(trifluoromethyl)imidazole lithium salt and mixing them evenly.
[0059] Example 10
[0060] The non-aqueous electrolyte of this embodiment is a non-aqueous solvent obtained by mixing EC, PC, DEC and EMC in a mass ratio of 5:25:30:30, adding NaPF6 at a molar concentration of 1.0 mol / L, and then adding 1.0% by mass of vinyl sulfate and 4-methylethylene sulfate, 0.5% by mass of 1-propenyl-1,3-sulfonic acid lactone, 5.5% by mass of sodium difluorooxalatoborate, and 1.0% by mass of 4,5-dicyano-2-(trifluoromethyl)imidazole lithium salt and mixing them evenly.
[0061] Embodiment 11
[0062] The non-aqueous electrolyte of this embodiment is a non-aqueous solvent obtained by mixing EC, PC, DEC and EMC in a mass ratio of 5:25:30:30, adding NaPF6 at a molar concentration of 1.0 mol / L, and then adding 1.0% by mass of vinyl sulfate and 4-methylethylene sulfate, 0.5% by mass of 1-propenyl-1,3-sulfonic acid lactone and sodium difluorooxalatoborate, and 0.05% by mass of 4,5-dicyano-2-(trifluoromethyl)imidazole lithium salt and mixing them evenly.
[0063] Example 12
[0064] The non-aqueous electrolyte of this embodiment is a non-aqueous solvent obtained by mixing EC, PC, DEC and EMC in a mass ratio of 5:25:30:30, adding NaPF6 at a molar concentration of 1.0 mol / L, and then adding 1.0% by mass of vinyl sulfate and 4-methylethylene sulfate, 0.5% by mass of 1-propenyl-1,3-sulfonic acid lactone and sodium difluorooxalatoborate, and 2.5% by mass of 4,5-dicyano-2-(trifluoromethyl)imidazole lithium salt and mixing them evenly.
[0065] Comparative Example 1
[0066] The non-aqueous electrolyte of this comparative example is a non-aqueous solvent obtained by mixing EC, PC, DEC and EMC in a mass ratio of 5:25:30:30, adding NaPF6 at a molar concentration of 1.0 mol / L, and then adding 0.5% by mass of sodium difluorooxalatoborate and 1.0% by mass of 4,5-dicyano-2-(trifluoromethyl)imidazole lithium salt and mixing them evenly.
[0067] Comparative Example 2
[0068] The non-aqueous electrolyte of this comparative example is a non-aqueous solvent obtained by mixing EC, PC, DEC and EMC in a mass ratio of 5:25:30:30, adding NaPF6 at a molar concentration of 1.0 mol / L, and then adding 1.0% by mass of vinyl sulfate and 4-methylethylene sulfate, 0.5% by mass of 1-propenyl-1,3-sulfonic acid lactone, and 1.0% by mass of 4,5-dicyano-2-(trifluoromethyl)imidazole lithium salt and mixing them evenly.
[0069] Comparative Example 3
[0070] The non-aqueous electrolyte of this comparative example is a non-aqueous solvent obtained by mixing EC, PC, DEC and EMC in a mass ratio of 5:25:30:30, adding NaPF6 at a molar concentration of 1.0 mol / L, and then adding 1.0% by mass of vinyl sulfate and 4-methylethylene sulfate, 0.5% by mass of 1-propenyl-1,3-sulfonic acid lactone and sodium difluorooxalate borate, and mixing them evenly.
[0071] Comparative Example 4
[0072] The non-aqueous electrolyte of this comparative example is a non-aqueous solvent obtained by mixing EC, PC, DEC and EMC in a mass ratio of 5:25:30:30, and NaPF6 is added at a molar concentration of 1.0 mol / L and mixed evenly.
[0073] The positive electrode sheet, the separator and the negative electrode sheet are stacked in order, and the separator is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role. The bare cells are stacked and placed in an outer package to prepare 5Ah soft-pack cells. The moisture content of the battery is controlled by controlling the cell baking time. The moisture content is the sum of the moisture in the baked positive and negative electrodes, the separator and the electrolyte to be injected of the cell tested by Karl Fischer titration. The mass fraction of the moisture in the cell is expressed in ppm, and the calculation method is the above-mentioned total moisture mass / (mass of the positive and negative electrode sheets+mass of the separator+mass of the electrolyte). The moisture content of the cells in Examples 1-5 is 400ppm, and the moisture content of the cells in Example 6 is 200ppm. Finally, the above-mentioned electrolyte is injected and packaged and formed to obtain a sodium ion battery.
[0074] The obtained sodium ion battery was subjected to a performance test: at 25°C, the sodium ion battery was charged to 3.95V at a constant current of 0.5C, then charged to 0.05C at a constant voltage at 3.95V, and discharged to 1.5V at a constant current of 0.5C, which was marked as discharge capacity C1. The battery was fully charged according to the above mode and placed in a 60°C oven for 7 days before being taken out and discharged to 1.5V at a constant current of 0.5C, which was marked as discharge capacity C2. The battery was then charged to 3.95V at a constant current of 0.5C, charged to 0.05C at a constant voltage at 3.95V, and discharged to 1.5V at a constant current of 0.5C, and the charge and discharge were repeated 3 times. The average value of the three discharge capacities was C3, and the capacity retention rate was (C2-C1) / C2*100%, and the capacity recovery rate was (C3-C1) / C2*100%.
[0075] At 25°C, the sodium ion battery is charged to 3.95V at a constant current of 0.5C, then charged to a current of 0.05C at a constant voltage, and then discharged to 1.5V at a constant current of 1C. The discharge capacity is recorded as the first capacity as C1. This process is repeated for cycle performance testing, and the capacity after 550 cycles is recorded as C 550 , Capacity retention rate (%) = C 550 / C1*100%;
[0076] At 25°C, the sodium ion battery is charged to 3.95V at a constant current of 0.5C, and then charged to 0.05C at a constant voltage of 3.95V to make it in a fully charged state of 3.95V. The thickness of the sodium ion battery with 100% SOC before storage is tested and recorded as D0. It is placed in a 60°C oven for 7 days and then taken out. The thickness of the sodium ion battery after storage is immediately tested and recorded as D1. The thickness expansion rate e = (D1-D0) / D0*100%;
[0077] The battery after 550 cycles was disassembled in a high-purity argon environment, the surface of the negative electrode was cleaned with dimethyl carbonate, the negative electrode coating was peeled off from the aluminum foil, collected and dried to constant weight, dissolved with nitric acid, and the metal ion content was detected by ICP to obtain the amount of transition metal dissolved;
[0078] The electrochemical properties of the sodium ion battery are shown in Table 1, and the metal ion content is shown in Table 2.
[0079] Table 1 Electrochemical performance of sodium ion batteries
[0080]
[0081]
[0082] Table 2 Transition metal dissolution of sodium ion batteries
[0083] Ni(ppm) Fe(ppm) Mn(ppm) Example 1 210 49 26 Example 2 184 40 27 Example 3 201 50 26 Example 4 198 42 24 Example 5 218 49 31 Example 6 203 48 29 Comparative Example 1 623 148 468 Comparative Example 2 615 152 453 Comparative Example 3 627 158 474 Comparative Example 4 723 196 564
[0084] As shown in Tables 1 and 2, Examples 1-6 combine three additives as composite additives to obtain a non-aqueous electrolyte, and the resulting sodium ion battery exhibits good cycle performance and high temperature storage performance, and the amount of transition metal dissolution is also small; Example 7 The composite additive uses a small amount of the first additive, and the SEI film formed on the surface of the positive and negative pole pieces of the sodium ion battery is easier to rupture, and the battery expansion cannot be effectively inhibited, resulting in repeated formation of the SEI film, causing a large amount of sodium ions to be consumed, and the cycle performance of the resulting sodium ion battery deteriorates; Example 8 The composite additive uses an excessive amount of the first additive, and the SEI film formed on the surface of the positive and negative pole pieces of the sodium ion battery is thicker, which increases the difficulty of sodium ion deintercalation, increases the side reactions, and increases the internal resistance of the battery, so that the charge and discharge efficiency and cycle performance of the resulting sodium ion battery are significantly reduced; Example 9 The composite additive uses a small amount of the second additive, and the SEI film formed on the surface of the positive and negative pole pieces of the sodium ion battery has poor stability, and the capacity decay of the sodium ion battery cannot be effectively inhibited, and the cycle performance of the resulting sodium ion battery deteriorates; Example 1 0 The composite additive uses an excessive amount of the second additive, the side reactions in the electrolyte system increase, the internal resistance of the battery increases, and the cycle performance of the obtained sodium ion battery deteriorates; Example 11 The composite additive uses a relatively small amount of the third additive, which cannot effectively capture water molecules, inhibit the hydrolysis of sodium salt in the electrolyte, reduce the ion conductivity of the electrolyte, slow down the transmission of sodium ions, and reduce the cycle performance of the obtained sodium ion battery; Example 12 The composite additive uses an excessive amount of the third additive, the side reactions in the electrolyte system increase, the internal resistance of the battery increases, and the cycle performance of the obtained sodium ion battery deteriorates; Comparative Examples 1-2 The electrolytes do not use the first additive and the second additive respectively, and the SEI film formed is less stable and easy to rupture, causing a large amount of sodium ions to be consumed, and the electrochemical performance of the obtained sodium ion battery deteriorates; Comparative Example 3 does not add the third additive and the electrolyte of Comparative Example 4 does not use additives, the inhibitory effect on the hydrolysis of the electrolyte components is weakened, more transition metals are dissolved, the SEI film formed on the surface of the positive and negative pole pieces of the sodium ion battery is destroyed, and the capacity decay of the obtained sodium ion battery is accelerated.
[0085] Figure 1The data of the cycle capacity retention curve show that in the early stage of the cycle, less water in the electrode enters the electrolyte, and the capacity retention rates of Example 1 and Comparative Example 3 are comparable. When the cycle exceeds 400 cycles, the amount of water in the electrode entering the electrolyte increases, resulting in the generation of HF and PF5, increased transition metal dissolution, and damage to the SEI film, which accelerates capacity decay.
[0086] Finally, it should be noted that the specific embodiments described herein are merely examples of the spirit of the present invention, and are not intended to limit the implementation methods of the present invention. Those skilled in the art of the present invention may make various modifications or supplements to the described embodiments or replace them in similar ways. It is not necessary and impossible to provide all examples of all implementation methods here. However, these obvious changes or modifications derived from the essential spirit of the present invention still fall within the scope of protection of the present invention, and interpreting them as any additional limitation is contrary to the spirit of the present invention.
Claims
1. A non-aqueous electrolyte, characterized in that: The invention comprises sodium salt, non-aqueous solvent and composite additives, wherein the composite additives comprise a first additive, a second additive and a third additive, wherein the first additive is a compound containing a sulfur-oxygen bond in its structure, the second additive is a sodium salt compound, and the third additive is an imidazole compound.
2. The non-aqueous electrolyte according to claim 1, characterized in that The first additive is one or more of cyclic sulfate compounds, cyclic sulfonate compounds, and fluorosulfonyl compounds; and / or the second additive is one or more of sodium difluorooxalatoborate, sodium difluorophosphate, sodium bis(fluorosulfonyl)imide, and sodium acesulfame.
3. The non-aqueous electrolyte according to claim 2, characterized in that The structural formula of the cyclic sulfate ester compound is wherein R1 to R4 are each independently a hydrocarbon group having 1 to 3 carbon atoms or a hydrogen atom, and n is 0 or 1; And / or the structural formula of the cyclic sulfonate compound is wherein R5 to R14 are each independently a hydrocarbon group having 1 to 3 carbon atoms, a hydrogen atom or a fluorine atom, Where n is 0 or 1, where n is 1; And / or the structural formula of the fluorosulfonyl compound is Here, R15 represents a hydrocarbon group having 1 to 6 carbon atoms, an aromatic group having 6 to 10 carbon atoms, or a fluorine atom.
4. The non-aqueous electrolyte according to claim 1 or 2, characterized in that: The mass of the first additive is 0.1-5.0% of the mass of the non-aqueous electrolyte; and / or the mass of the second additive is 0.1-10.0% of the mass of the non-aqueous electrolyte.
5. The non-aqueous electrolyte according to claim 1, characterized in that The cation of the third additive is one or more of lithium ion, sodium ion, imidazolium cation, and quaternary ammonium cation, and the anion is an imidazolium anion.
6. The non-aqueous electrolyte according to claim 1 or 5, characterized in that: The mass of the third additive is 0.1 to 2.0% of the mass of the non-aqueous electrolyte.
7. The non-aqueous electrolyte according to claim 5, characterized in that The structural formula of the imidazolium cation is The structural formula of the quaternary ammonium cation is Here, R16 to R19 each independently represent a hydrocarbon group having 1 to 6 carbon atoms.
8. The non-aqueous electrolyte according to claim 1, characterized in that The concentration of the sodium salt in the non-aqueous electrolyte is 0.5-2.0M.
9. The non-aqueous electrolyte according to claim 1, characterized in that The non-aqueous solvent is one or both of carbonate ester and carboxylate ester.
10. A sodium ion battery, characterized in that: The invention comprises a positive electrode sheet, a negative electrode sheet, a separator and the non-aqueous electrolyte according to claim 1.